MEMS Pitch Gyroscope Based on (250-nm)² Gauges Achieving 0.12 °/hr Over 1000 dps Full-Scale - Buffoli, Andrea; Gadola, Marco; Robert, Philippe; Langfelder, Giacomo (Journal of microelectromechanical systems, 2024)
This document presents a novel architecture of a microelectromechanical system (MEMS) gyroscope for in-plane angular rate sensing (i.e. pitch or roll axis), with a detailed characterization of the performance, including effects of etching nonuniformities and quadrature, which are relevant when dealing with these specific sensing axes. The adopted technology features 20- μ m-thick frames and springs, and 250-nm-thick and -wide resistive gauges, which are subject to stress under Coriolis-force-induced tilt of a torsional lever. The new design increases by a factor larger than 3 the efficiency of the transduction between tilting of the Coriolis frame inside the gyroscope and corresponding stress on the resistive gauges, in turn improving scale-factor, and bringing noise and stability down to record levels for pitch or roll planar silicon micromachined gyroscopes. At the same time, with respect to a former architecture, a comparative analysis of the impact of the new design choices on the dispersion of the mode-split value is carried out. Results demonstrate that the dispersion increases by a negligible amount, from 36 Hz (old design) to 44 Hz (new design). Most of tested gyroscopes have quadrature value within 5000 dps: however, within a 6-V supply operated board, only part of these sensors could be properly operated under automatic quadrature compensation, reaching under these conditions noise in the range of 0.02~^{° } / \surd hr and the minimum of the Allan deviation at 0.12~^{° } /hr.[2024-0124]